A case report and literature review of the late presenting congenital diaphragmatic hernia. Issue 3 (July 2018) - Kalvandi, Gholamreza; Shahramian, Iraj; Bazi, Ali; Razavipour, Seyed Mohammad Kazem; Delaramnasab, Mojtaba
Abstract : Late presenting congenital diaphragmatic hernia is a disease associated with defective diaphragm and penetration of different organs into the thoracic cavity. In the present case, a 3-year-old boy was referred to our hospital complaining of acute abdominal pain. No other gastrointestinal symptoms including nausea, vomiting, or constipation were observed. The patient represented no respiratory problems such as dyspnea or respiratory distress syndrome. Radiograph of the thoracic and abdominal cavities showed bowel loops occupying the entire space of the left hemithorax and right-shifted mediastinum. The patient was referred to the pediatric surgery center. The defect was resolved by prompt surgical intervention. A follow-up radiograph within 6 months of surgery showed complete recovery.